Rancang Bangun Aplikasi Pendukung Pembelajaran Ilmu Pengetahuan Sosial (IPS) Sekolah Dasar Berbasis Android - Dinda Bahari Putri; Sri Endang Anjarwani; Royana Afwani (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
IPS is a lesson at the elementary school level. Based on the curriculum at SDN 22 Ampenan which uses the 2006 KTS curriculum, each student learns to use the media of LKS and books as the supporting media. The availability of the media has less influence on students. The purpose of this research is to develop an Android-based application which can support the school. This application aims to help the learning process of students with multimedia available in the application. This application displays materials, images, videos, and evaluations which are contained in the exercises and games of each chapter in grades 5 and 6.This application is built using android studio version 2.2.1 with the Java programming language. Besides this application is also developed using the waterfall model. The testing method used is a black box and MOS testing. Testing using the MOS method on application quality shows that 62.5% of the respondents stated strongly agree, teacher respondents stated strongly agree with the percentage of 62.75%.